STRES AKADEMIK DENGAN NYERI LEHER DAN BAHU PADA MAHASISWA TINGKAT AKHIR DI STIKES KARYA HUSADA KEDIRI - Vivi Alaida Najwa; Andika Siswo Ariwibowo; Dwi Setyorini (STIKES dan AKZI Karya Husada Kediri, 2022)
One form of stress that is often experienced by students and college students is academic stress. Stress can cause neck and shoulder pain due to psychological pressure which causes tension in the muscles, causing a person to experience pain easily. Stress causes a decrease in blood around the trape zius muscle and increases the flow of electricity so that the muscle contracts and muscle spasms occur. The purpose of this study was to determine the correlation between academic stress and neck and shoulder pain in final year students at STIKES Karya Husada Kediri. The design of this research is correlational with a cross sectional approach. The population is 176 students, 53 samples were obtained using the proportionate stratified random sampling technique. Collecting data using PAS (Perception Of Academic Stress) questionnaire and measurement of pain using NRS (Numeric Rating Scale). The results showed that more than half (56.6%) experienced academic stress in the moderate category. And more than half (64.2%) experienced moderate level of neck and shoulder pain. Spearman rank statistical test results obtained p-value of 0.001 < α=0.05 with r: -0.432 with a negative relationship direction, meaning that the higher the academic stress, the lower the neck and shoulder pain. Students experience moderate academic stress due to academic expectations such as competition between students, lecturers' expectations, and high parental expectations of student achievement. It is hoped that students will be able to adapt and divide their time and manage stress by improving their coping strategies.